Dark Patterns: Social Media, Gaming, and E-Commerce. (September 2021) - Karagoel, Ilayda; Nathan-Roberts, Dan
Dark Patterns are defined as "tricks used in websites and apps that make you do things that you didn't mean to" (Bringull, 2017). They are implemented to manipulate users with deceptive design tactics using studies on human behavior, and are coined as "anti-user", since the marginal benefit of corporations are being prioritized over users. This proceeding specifically studies the prevalent dark patterns in the fields of Social Media, Gaming, and E-Commerce platforms. Though Grey et al. initially characterized dark patterns into 12 types of dark patterns (Gray et al., 2018), there are plenty of studies where more categorizations of dark patterns are found in different fields. Finally, this paper sheds light on what could be the next steps for the stakeholders, such as designers, engineers and the overall socio technical system, to better regulate dark patterns in order to minimize user concerns, as well as reduce unethical design practices.